Hiring Juvenile Delinquents: Employer Callbacks from a Correspondence Study (Journal of Applied Juvenile Justice Services, 2020)
Employers are less likely to call back job applicants with criminal records; however, few studies have examined the impact of a delinquency history on employment outcomes in adulthood. Historically, juveniles have been protected from stigmas associated with delinquent records, as state policies allowed for the sealing or expungement of records. However, juveniles could nowface similar stigmas as adults, as states are increasingly limiting the expungement protections for juvenile delinquents; juveniles are frequently posting personal information online; juveniles could feel pressured by potential employers to disclose a delinquency history; and juveniles transferred into criminal court do not receive record protections. A correspondence study was conducted using two fictitious resumes sent to employers in Northern Nevada, one with a delinquency history and one without a delinquency history. Unexpectedly, employers showed no bias toward delinquent applicants in the current study. Explanations for this finding, policy implications, and directions for future research are discussed.